2014
DOI: 10.5604/20831862.1133937
|View full text |Cite
|
Sign up to set email alerts
|

Body Structure and Composition of Canoeists and Kayakers: Analysis of Junior and Teenage Polish National Canoeing Team

Abstract: The somatic build, biological age, general state of health, mental predisposition and physical fitness are the criteria for selection of individuals in competitive sport. The present study aims to analys the differences in body structure and composition of canoeists and kayakers and derive conclusions regarding the criteria for selection of individuals incompetitive sport. The research was conducted on a group of 32 men aged between 17 and 22: 16 kayakers and 16 Canadian canoeists of the junior and teenage Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
2
10
2
Order By: Relevance
“…In sports dominated by strength characteristics we find the mesomorph component, as authors have shown in the case of Polish judokas with a somatotype 3.5-5,9-1,8, which is very representative (Lewandowska, Buśko, Pastuszak, & Boguszewska, 2011). The mesomorph component is related to individual sports which require muscle strength (Stanković, Pavlović, Petković, Raković, & Puletić, 2018;Hagner-Derengowska et al, 2014;Sterkowicz-Przybycień, Sterkowicz, & Żarów, 2011;Mathur, Toriola, & Igbokwe, 1985), and the ectomorph for group sports where precision and skill are required (Carvajal et al, 2012;Malousaris et al, 2008;Mathur et al, 1985).…”
Section: Introductionsupporting
confidence: 57%
“…In sports dominated by strength characteristics we find the mesomorph component, as authors have shown in the case of Polish judokas with a somatotype 3.5-5,9-1,8, which is very representative (Lewandowska, Buśko, Pastuszak, & Boguszewska, 2011). The mesomorph component is related to individual sports which require muscle strength (Stanković, Pavlović, Petković, Raković, & Puletić, 2018;Hagner-Derengowska et al, 2014;Sterkowicz-Przybycień, Sterkowicz, & Żarów, 2011;Mathur, Toriola, & Igbokwe, 1985), and the ectomorph for group sports where precision and skill are required (Carvajal et al, 2012;Malousaris et al, 2008;Mathur et al, 1985).…”
Section: Introductionsupporting
confidence: 57%
“…Vedat (2012) proceeded in the same inconsistent manner, studying the anthropomorphic parameters of the Turkish national kayak and canoe white-water slalom team and presenting the results for all men's kayak and canoe categories together. These categories, however, differ in the demands they place on athletes' strength, and it is thus not appropriate to combine data from the various categories together (Bílý, 2002), as previous researchers have shown that the anthropometric parameters and somatotype are different between kayakers and canoeists (Hagner-Derengowska et al, 2014). In the study by Bílý, Süss, & Buchtel (2011), the categories were properly separated, but the number of anthropometric parameters tracked was very low and the authors used bioelectrical impedance to measure the athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore some authors failed to provide information about measurements performed in their studies,[4, 13, 24]. It seems that such errors are generated in papers published in journals with high impact factors,[45, 8, 10–11, 13, 20, 22–23, 2628, 32–33, 39, 51] as well as “less prestigious” ones,[16, 2425, 34, 36, 38, 4446, 50].…”
Section: Discussionmentioning
confidence: 99%
“…The supraspinale skinfold method defines this skinfold as a diagonal fold raised five to seven centimetres above the anterior superior iliac spine on a line to the anterior axillary border and on a diagonal line going downwards and inwards at 45°,[1–2, 37]. Many researchers,[20, 27, 34–35, 38–39] have measured the iliac crest skinfold as a diagonal fold raised immediately above the crest of the ilium on a vertical line from the mid-axilla,[37]. Measured in the same way, the suprailiac skinfold was referred to body fat evaluated by Durnin and Womersley,[40].…”
Section: Introductionmentioning
confidence: 99%